Development of competency profile for records managers in the Malaysian Federal Ministries / Asmadi Mohammed Ghazali - Mohammed Ghazali, Asmadi (Institute of Graduate Studies, UiTM, 2012)
This study was undertaken with the aim to explore the competency profile of the records manager in Malaysian federal ministries. Problem statements, identified from review, include: (a) the advancement of Information & Communication Technology, (b) incompetent records managers, and (c) unavailability of Malaysian records manager competency profiles. Knowledge, skills and attitudes define competence. As the exploratory sequential approach concerns research methodology, the first phase of data collection involves contents analysis technique and on-line focus group discussions. Four competencies manual from United Kingdom, United States, Canada and Australia; and qualitative data from on-line focus groups discussions were transcribed and categorized to identify themes and patterns by applying manifest and latent coding. In the second phase, the data collected from aforementioned methods has been used to develop a survey questionnaire which drew the response of 182 Departmental Records Officer from 25 federal ministries. The mean ranking and descriptive statistics were used to analyze quantitative data.